2014
DOI: 10.1007/s11325-014-1068-8
|View full text |Cite
|
Sign up to set email alerts
|

A promising concept of combination therapy for positional obstructive sleep apnea

Abstract: PurposeThe objective of this randomized controlled trial was to assess the additional effect of a chest-worn sleep position trainer (SPT) in patients with residual supine-dependent obstructive sleep apnea (sdOSA) under mandibular advancement device (MAD) therapy.MethodsBaseline and follow-up polysomnography with MAD were performed. Twenty patients with sdOSA under MAD therapy underwent two consecutive randomized polysomnographies: one with SPT and one with combination of SPT + MAD. Data are presented as median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 31 publications
4
69
0
2
Order By: Relevance
“…Although this study was only conducted in five patients with severe OSA, it provided initial support for the concept that combination therapy may be viable in treating OSA. Similarly, Dieltjens et al 38 demonstrated the additional reduction in OSA severity patients experienced when sleeping in the lateral position was done in conjunction with wearing an oral appliance. Last, Oliven et al 39 assessed the effect of a combination of electrical stimulation of the genioglossus with mandibular advancement (targeting muscle responsiveness and anatomy/collapsibility respectively) on the Pcrit in 14 OSA patients under propofol-induced anesthesia.…”
Section: Does Combination Therapy Have a Future In Sleep Medicine?mentioning
confidence: 95%
“…Although this study was only conducted in five patients with severe OSA, it provided initial support for the concept that combination therapy may be viable in treating OSA. Similarly, Dieltjens et al 38 demonstrated the additional reduction in OSA severity patients experienced when sleeping in the lateral position was done in conjunction with wearing an oral appliance. Last, Oliven et al 39 assessed the effect of a combination of electrical stimulation of the genioglossus with mandibular advancement (targeting muscle responsiveness and anatomy/collapsibility respectively) on the Pcrit in 14 OSA patients under propofol-induced anesthesia.…”
Section: Does Combination Therapy Have a Future In Sleep Medicine?mentioning
confidence: 95%
“…Although positional therapy effectiveness has traditionally been limited to in those with mild to moderate positional OSA (POSA; Jokic, Klimaszewski, Crossley, Sridhar, & Fitzpatrick, 1999;Permut et al, 2010;van Maanen et al, 2013) favorable outcomes have also been reported in those with severe POSA so long as the patient stays off his or her back (Levendowski et al, 2014). It has also been demonstrated that supine avoidance reduces Cheyne-Stokes breathing in heart failure patients with central sleep apnea (Joho, Oda, Hirai, & Inoue, 2010;Soll et al, 2009) and increases the therapeutic response when combined with other OSA therapies (Dieltjens et al, 2015;Lee et al, 2011). Thus, the majority of patients with sleep apnea would receive therapeutic benefit if they could be behaviorally trained to avoid supine sleep.…”
mentioning
confidence: 99%
“…An intention-to-treat analysis was performed in four studies 6,11,28,29 ; one was a per protocol analysis 35 and in the remaining two no specifics were mentioned. 30,34 In one of these two there was no loss to followup, 30 and in the other five patients withdrew. …”
Section: 30mentioning
confidence: 88%
“…Both devices have the capacity to store and register data, such as sleeping posture, that can be uploaded through custom software via a USB connection and personal computer. 6,11,30,34,35 Concerning the neck-worn devices, the device (see Figure 4) described by van Maanen et al 28 consisted of a small vibrating apparatus (30 × 30 × 10 mm, powered by three small batteries). The position sensor provides a vibrating stimulus with a delay of 10 seconds after the supine position is detected, causing the device to vibrate with gradual incremental strength until a different sleeping position is detected, in which case the vibrations ceased immediately.…”
Section: Control Tbtmentioning
confidence: 99%
See 1 more Smart Citation